Effect of low-dose blanched Saccharina latissima in finishing bulls’ diets on carcass and meat quality traits - Grabež, Vladana; Mydland, Liv Torunn; Papoutsis, Dimitrios; Øverland, Margareth; Egelandsdal, Bjørg (Frontiers in Animal Science, 2023)
Nutritional and bioactive compounds present in seaweeds make them suitable supplements or feed ingredients in livestock diets. This study assessed the effect of blanched seaweed (Saccharina latissima) as a supplement in finishing bulls’ diets on carcass traits and the quality of the longissimus lumborum (LL) and semimembranosus (SM) muscles. A concentration of 0.8% dry matter of blanched S. latissima in bulls’ diets was the maximum amount allowed, owing to iodine and arsenic thresholds in animal feed. Nineteen Limousin crossbreed bulls were randomly assigned to two groups, fed a control (CD, n = 9) diet or a test diet supplemented with blanched seaweed (SW, n = 10), and fed for 48 days pre slaughter. The carcasses from the bulls finished on a seaweed-supplemented diet were heavier (p < 0.05) than those in the control group, while levels of conformation and fatness were similar between the groups (p > 0.05). The pH was lower (p < 0.05) in the LL of CD-fed animals in early post mortem than in the LL of SW-fed animals, whereas no differences (p > 0.05) were found in the ultimate pH. The meat from the bulls fed both diets had a similar (p > 0.05) drip loss and shear force at days 7 and 14. The cooking loss at day 7 was not affected (p > 0.05) by diet, whereas on day 14 the cooking loss was greater (p < 0.05) for SW than for CD meat. Warmed-over flavor and shear force were muscle dependent and lower (p < 0.05) for LL than SM. Seaweed supplementation in finishing bulls’ diets had no clear effect on color changes (L*, a*, and b* values) during chilled storage, although reduced b* values (p < 0.05) suggest an improved color stability of meat from SW- compared with CD-fed animals. The iodine content was higher (p < 0.05) in the SW meat than in the CD meat, even when using the low seaweed supplementation level requested by the authorities. A small increase of arsenic in the meat with seaweed supplementation has no implications on human health. Cost-efficient processing methods for the further reduction of iodine and arsenic are needed to increase the utilization of seaweed as a feed additive/ingredient and attain a clear effect on meat quality.